Performance of polycrystalline GaN based metal-semiconductor-metal (MSM) photodetector with different contact. (February 2020) - Zainal, N.; Ahmad, M.A.; Maryam, W.; Samsudin, M.E.A.; Waheeda, S.N.; Taib, M. Ikram Md.; Hassan, Z.
Abstract: This paper describes performance of polycrystalline GaN based metal-semiconductor-metal (MSM) photodetector using different contact; Al, ITO, Ni and Pt. The performance of each photodetector was investigated in term of electrical resistivity ( ρ ), signal-to-noise ratio (SNR), responsivity ( R ), internal quantum efficiency ( η ) and temporal responsivity. From the results, Ni is suggested to be a good contact for the photodetector. This is due to diffusion of Nix O, formed by residual oxides on the GaN layer, into the Ni contact reduced the resistivity, thereby increasing the electrical conductivity of the photodetector. The photodetector with Ni contact demonstrated significant increase in SNR behavior with increasing bias voltage, while its ρ value was measured to be 2.02 MΩ cm 2, and η was 3.13%, 2.36% and 1.52%, at λ = 342 nm, 385 nm and 416 nm, respectively. From the temporal responsivity measurement, the rise time = 1.75 s, the recovery time = 1.87 s and the sensitivity = 5840%. Highlights: Ni is a good electrical contact to polycrystalline GaN based MSM photodetector. Nix O inclusions in Ni leads to improving the performance of the photodetector. All photodetectors have extended the cut-off wavelength.